Kajian Spasial Perencanaan Lokasi Sarana Kesehatan Milik Pemerintah Berdasarkan Proyeksi Kebutuhan di Kota Salatiga Tahun 2016-2035 - Pratiwi, Andri, Drs. Priyono, M.Si (2016)
Salatiga is an area of town that has experienced the regional growth in 1992 due to the increasing number of population growth. This population increases resulted the population activity is also increasing in various fields so the need of health services has also increased. This led to the availability of public health facility become one of the priorities in an effort to meet the health care needs of the population. This study aims to assess the condition of the existing distribution locations in public health facility in Salatiga in the year of 2016 and also assess the location plan in public health facility in Salatiga in the year of 2016-2035. The data used is the rate of population growth data, population projection data in 2035, and the need projection data of the population against the public health facility. The method used is sensus method of the General Hospital, Maternity Hospital, Health Centers, and Sub Health Center in Salatiga and overlay method with techniques utilizing Geographic Information Systems (GIS). Spatial sudy of public health facility location plan refers to the spatial distribution pattern, accessibility, and SNI 03-1733-2004 by observing into the criteria of service life of the population, the floor area and land area, settlement location, as well as the designation of the land from Peta Rencana Pola Ruang of RTRW Salatiga in the year of 2011-2030. The results showed that the condition of the existing distribution locations of public health facility is 3 General Hospital, 0 Maternity Hospital, 6 Health Centers, and 20 midwife maternity homes then the lack of public Maternity Hospital can be Sub Health Center that had clumped distribution pattern with the T value is 0.63. The level of accessibility in public health facility will be higher when the distance is getting closer, situated on the edge of the road, and provided adequate means of transportation. The need projection of the population shows the need for 10 units of public Maternity Hospital, but the presence of 1 (one) private Maternity Hospital and 106 resolved so that has not required the addition of new units until 2035.